Transcriptome analysis of sugarcane reveals differential switching of major defense signaling pathways in response to Sporisorium scitamineum isolates with varying virulent attributes - Agisha, V.N.; Ashwin, N.M.R.; Vinodhini, R.T.; Nalayeni, Kumaravel; Ramesh Sundar, Amalraj; Malathi, Palaniyandi; Viswanathan, Rasappa (Frontiers in Plant Science, 2022)
Sugarcane smut caused by the basidiomycetous fungus Sporisorium scitamineum is one of the most devastating diseases that affect sugarcane production, globally. At present, the most practical and effective management strategy for the disease is the cultivation of resistant cultivars. In this connection, a detailed understanding of the host’s defense mechanism in response to smut isolates with varying degrees of virulence at the molecular level would facilitate the development of reliable and durable smut-resistant sugarcane varieties. Hence, in this study, a comparative whole transcriptome analysis was performed employing Illumina RNA-seq in the smut susceptible cultivar Co 97009 inoculated with two distinct S. scitamineum isolates, Ss97009 (high-virulent) and SsV89101 (low-virulent) during the early phases of infection (2 dpi and 5 dpi) and at the phase of sporogenesis (whip emergence) (60 dpi). Though the differential gene expression profiling identified significant transcriptional changes during the early phase of infection in response to both the isolates, the number of differentially expressed genes (DEGs) were more abundant at 60 dpi during interaction with the high virulent isolate Ss97009, as compared to the low virulent isolate SsV89101. Functional analysis of these DEGs revealed that a majority of them were associated with hormone signaling and the synthesis of defense-related metabolites, suggesting a complex network of defense mechanisms is being operated in response to specific isolates of the smut pathogen. For instance, up-regulation of hormone-related genes, transcription factors, and flavonoid biosynthesis pathway genes was observed in response to both the isolates in the early phase of interaction. In comparison to early phases of infection, only a few pathogenesis-related proteins were up-regulated at 60 dpi in response to Ss97009, which might have rendered the host susceptible to infection. Strikingly, few other carbohydrate metabolism-associated genes like invertases were up-regulated in Ss97009 inoculated plants during the whip emergence stage, representing a shift from sucrose storage to smut symptoms. Altogether, this study established the major switching of defense signaling pathways in response to S. scitamineum isolates with different virulence attributes and provided novel insights into the molecular mechanisms of sugarcane-smut interaction.